Pre‐pregnancy Cardiovascular Health and Adverse Pregnancy Outcomes After Frozen Embryo Transfer: A Retrospective Cohort Study - Fengyi Ren; Wen Zhang; Mengyao Qin; Xin Liu; Zixuan Zhang; Fei Zhao; Lei Sheng; Ling Geng; Xinxia Chen (Paediatric and Perinatal Epidemiology, 2026)
ABSTRACT Background Cardiovascular health before pregnancy may influence maternal and pregnancy outcomes; however, evidence among women undergoing frozen embryo transfer (FET) remains limited. Objective This retrospective cohort study aims to investigate the association between pre‐pregnancy biomedical cardiovascular health (CVH), defined by the American Heart Association, and adverse pregnancy outcomes (APOs) after FET. Methods This retrospective cohort study was conducted from January 2019 to August 2023 and included 1521 women undergoing FET in their first in vitro fertilisation/intracytoplasmic sperm injection (IVF/ICSI) cycle. The main APOs included hypertensive disorders of pregnancy (HDP), gestational diabetes mellitus (GDM), preterm birth (PTB), offspring being large for gestational age (LGA) and small for gestational age (SGA). Modified Poisson regression models with restricted cubic splines were used to investigate the relationship between biomedical CVH and APOs, and adjusted population‐attributable fraction (PAF) and partial population‐attributable fraction(partial PAFs) models were used to quantify the theoretical reduction in APOs with CVH improvement. Results Compared with the high CVH group, the low‐to‐moderate CVH group was associated with higher risks of HDP (relative risk [RR] 2.61, 95% confidence interval [CI] 1.83, 3.73), GDM (RR 1.82, 95% CI 1.40, 2.38), PTB (RR 2.03, 95% CI 1.47, 2.81), and LGA (RR 1.28, 95% CI 1.08, 1.52). CVH was linearly associated with the log risk of HDP and PTB. In contrast, CVH showed nonlinear associations with the log risk of GDM and LGA. PAF estimates suggest that 11.0%–36.1% of these APOs could be associated with low‐to‐moderate CVH (CVH score < 80). Specifically, for individual CVH components, elevated blood pressure was the leading risk factor for HDP, whereas overweight and obesity (BMI) were the strongest risk factors for GDM, PTB, and offspring LGA. Conclusions Biomedical CVH is negatively associated with APOs in pregnancies after FET. Women undergoing FET might benefit from preventive strategies to improve CVH, especially BMI and blood pressure.